Is Readiness to Take Action Among Women in Violent Relationships a Catastrophic Phenomenon?. Issue 7 (April 2020) - Katerndahl, David A.; Burge, Sandra K.; Ferrer, Robert L.; Becho, Johanna; Wood, Robert
Taking action among women in violent relationships appears to involve sudden changes and reversals after periods of building stress, suggesting that decision making is a "catastrophic" phenomenon. This study sought to determine whether readiness-to-change is best modeled as a cusp catastrophic (CCM) phenomenon among women in violent relationships. A total of 143 women who experienced violence in the previous month completed baseline and end-of-study interviews assessing her hope, coping strategies, social network, and readiness-for-action (seeking help, taking legal action, and leaving) concerning the violence. Daily assessments of his violent behavior, forgiveness sought and given, and her perceived need-for-action were collected via telephone Interactive Voice Response for 8 weeks. Using regression analysis, the impact of factor-analyzed asymmetry (violence burden) and bifurcation (hope and cope, support, forgiveness, and number of children) variables on the outcomes (readiness-for-help, legal action, and leaving) was modeled, comparing the CCM against linear models to determine which model accounts for the most variance in each outcome. Cusp catastrophe models for all three actions accounted for more variance than either linear model comparison, but violence burden was only relevant to readiness-for-help and different bifurcation variables were at work for each action. While forgiveness was an important bifurcation factor in readiness-for-help and number of children served as the bifurcation factor for readiness-for-legal-action, readiness-to-leave was more complex with both number of children and hope-and-cope as bifurcation factors. Not only should we expect sudden changes in readiness but efforts to facilitate decision making should focus on addressing the bifurcation factors that may distort her interpretation of reality.